2017
DOI: 10.1055/s-0037-1603782
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Access Appropriate Information Online?

Abstract: Health care providers should be aware of information available on the Internet to ensure proper patient care. The current analysis assesses the reliability, quality, and readability of internet information describing rhytidectomy. Previously validated survey instruments to assess the reliability, quality, and readability of online websites describing rhytidectomy were used. An internet search using Google with the search term “facelift” was conducted. The first 50 search results were reviewed, and 36 were deem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The classification of results in search engine searches is based on complex algorithms whose adopted mechanism is not well-publicized. It is believed that the position of electronic websites in the ranking is mainly associated with user traffic, involving the number of visitors and page popularity, and not with their information quality (Arif & Ghezzi, 2018;Gupta et al, 2017;Yeung & D'Souza, 2013). This tends to influence lay users always to access the first pages, considering popularity over quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification of results in search engine searches is based on complex algorithms whose adopted mechanism is not well-publicized. It is believed that the position of electronic websites in the ranking is mainly associated with user traffic, involving the number of visitors and page popularity, and not with their information quality (Arif & Ghezzi, 2018;Gupta et al, 2017;Yeung & D'Souza, 2013). This tends to influence lay users always to access the first pages, considering popularity over quality.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring reference established by Charnock et al (1999) in the DISCERN questionnaire was used to website's level quality. It is considered a three-point descriptive scale, similar to that carried out in other studies (Gupta et al, 2017;Yeung & D'Souza, 2013). For each sentence, the presence or absence of the evaluated criterion on the websites selected was verified, with up to three possibilities of answers linked to a given score: absence -one (1); partial presence -two…”
Section: Methodsmentioning
confidence: 99%
“…It was designed to assess the reliability of medical information and to evaluate the quality of medical treatment information. In recent years the system has been used by different sub‐disciplinary medical teams to evaluate the quality of English patient‐education information for several chronic diseases, showing a good applicable value, and has gradually been promoted by the academic community as one of the core evaluation systems . However, its feasibility in Chinese patient‐education information has not been determined so far.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the system has been used by different sub-disciplinary medical teams to evaluate the quality of English patient-education information for several chronic diseases, showing a good applicable value, and has gradually been promoted by the academic community as one of the core evaluation systems. 9,10,14 However, its feasibility in Chinese patienteducation information has not been determined so far. Our study showed a good consistency of each evaluation part with all Spearman coefficients above 0.55, suggesting that it could be used as one Chinese patient-education information evaluation system among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation